Riesgos psicosociales y estrés laboral en el personal de salud Hospital Básico “Asdrúbal De la Torre”- 2020: Psychosocial risk factors and work stress in health personnel Asdrúbal de la Torre Basic Hospital- 2020 (La U Investiga, 2020)
Work-related stress is considered a health problem that has a negative impact on the health of different age groups of workers and is very common among health professionals, predominantly affected and showing various psychosocial risks, with a high cost in terms of health. A non-experimental, quantitative, descriptive and relational study was carried out, in which 45 health workers, belonging to the entire payroll of the “Asdrúbal de la Torre” Basic Hospital, were evaluated during the period April-September 2019. To To estimate the relationship between psychosocial risks and work stress, the psychosocial risks questionnaires by Noemí Silva and the work stress questionnaires by Carmen Villalobos were applied, finally correlating their variables.Statistical significance was determined between the symptoms of social behavior and social interaction with organizational aspects (p = 0.01) and performance remuneration (p = 0.02). Likewise, intellectual and work symptoms had a statistically significant relationship with work condition (p = 0.03), and workload (p = 0.04). A statistically significant relationship was demonstrated between the symptoms of social behavior and the employee’s length of service (p = 0.00), showing the existence of a significant relationship between work stress and burnout syndrome in the personal respondent.
Keywords: Work stress; quality of life; psychosocial risks; occupational health